Lze při zohlednění subjektivního a objektivního kritéria menšinové definice příslušníky LGBTI komunity považovat za menšinu? - Markéta Polendová (Acta Universitatis Carolinae. Iuridica, 2024)
The publication focuses on the status of LGBTI persons in the context of minority law, which is traditionally associated with national, linguistic, and religious minorities. It aims to evaluate the potential of the LGBTI community to fulfil the defining characteristics of a minority. The author analyses the features of the minority definition, i.e., the objective and subjective criterion, and subsequently evaluates the possibility of fulfilment of the individual characteristics by the LGBTI community. Problematic aspects arising in connection with the specific nature of the LGBTI community, especially its internal diversity and the difficult objectification of the differentiating characteristics of individual members, are emphasised. The author concludes that provided the specific features are dully considered, the LGBTI community in principle meets both the objective and the subjective criterion of the minority definition.